2019
DOI: 10.1177/2309499018821774
|View full text |Cite
|
Sign up to set email alerts
|

Matching precision of the reverse contralateral radial head in generating of the individualized prosthesis from the surface registration in tuberosity-neck and in tuberosity-diaphysis

Abstract: Purpose: Following the radial head replacement, the surface mismatches between the implants and the morphological characteristics of the original proximal radius decreased contact areas and increased contact forces which is potential for the long-term articulating cartilage wear. Several studies demonstrated that the individualized prosthesis, created from computed tomographic (CT) images of the contralateral side with the reverse engineering technology, may reduce the mismatch. The aim of this study is to dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…This study revealed also that the estimation of the Rh implant height on lateral radiographs is poorly reproducible among surgeons (ICC: 0.443) [36]. CT scans, when available, can provide additional information on Rh anatomy and guide the surgeon towards the appropriate size planning [13,[36][37][38].…”
Section: Discussionmentioning
confidence: 88%
“…This study revealed also that the estimation of the Rh implant height on lateral radiographs is poorly reproducible among surgeons (ICC: 0.443) [36]. CT scans, when available, can provide additional information on Rh anatomy and guide the surgeon towards the appropriate size planning [13,[36][37][38].…”
Section: Discussionmentioning
confidence: 88%
“…Based on the symmetry of the human skeleton, we can reverse the 3D images of the normal bone to the contralateral side to create the anatomic prosthesis for the missing part. 12 Using this technique, the tailor-made prostheses for several bones and joints have been previously reported. 13,14 The recent biomechanic study in the cadaveric arms demonstrated that the reverse-engineered distal humeral hemiarthroplasty prostheses did not reproduce the same contact pattern as the native joints, possibly because the prostheses were designed based on distal humeral osseous anatomy from the CT images which is lacked inclusion of the cartilage thickness.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Based on the symmetry of the human skeleton, the 3D images of normal radial head can be reversed to manufacture the prosthesis of contralateral side which has the accurate shape and dimension for the missing part. 10 In addition, 3D preoperative planning can be used to generate the intraoperative guide in order to implant the prosthesis in the correct position. 8 A previous morphological analysis demonstrated that, in the setting of ideal prosthetic placement, the patient-specific implants generated from the contralateral intact radial head had less surface mismatch than the commercially available designs.…”
Section: Introductionmentioning
confidence: 99%